Dietary Consumption of Virgin Coconut Oil Ameliorates Lipid Profiles in Diabetic Rats. (29th September 2014) - Akinnuga, A. M.; Jeje, S. O.; Bamidele, O.; Sunday, V. E.
Abstract : Virgin coconut oil (VCO) is a saturated fat with promising antidiabetic properties but its ameliorative effect on lipid profiles in diabetics is rarely reported. Therefore, in this study, a total of fifteen (15) male rats weighing 200–250 g were divided into 3 experimental groups (n = 5 ). Group I (control) and Group II (diabetic control group) were fed a normal rat chow while Group III (diabetic test group) was fed a 10% VCO diet for 3 weeks. Group II and Group III were made diabetic by intraperitoneal injection of 150 mg/kg of alloxan. After 72 hours of injection, blood glucose was tested to confirm diabetes mellitus. After 3 weeks, the animals were sacrificed to collect blood samples for lipid profile analysis. The results showed a significant increase in concentrations of triglyceride, total cholesterol, low density lipoprotein, and very low density lipoprotein and decrease in concentration of high density lipoprotein in Group II when compared to Group I. Also, the concentrations of triglyceride, total cholesterol, low density lipoprotein, and very low density lipoprotein except high density lipoprotein significantly reduced in Group III when compared to Group II (P < 0.01, 0.001). VCO consumption can be claimed to ameliorate lipid levels in diabetes mellitus.